La "Historik" de J. G. Droysen: un puente entre la investigación empírica y la fundamentación teórica del conocimiento histórico - Joseph Dager Alva (Memoria y Civilización, 2004)
This paper analyzes the Historik of the renowned historian Johann Gustav Droysen (1808-1884), professor at the universities of Berlin, Gena and Kiel, from a historiographic perspective. We postulate that Droysen, not only offered lessons about the method to study the past, but also tried to sustain the autonomy and independence of the historical discipline from philosophy and natural science. In that sense, Droysen followed the path established by the German historical school and went one step beyond, formulating a theoretical approach to understand how historical knowledge is acquired, coinciding sometimes with the subsequent philosophical movement called German historicism. Although he strongly questioned the notion of "historical fact", he didn’t conceive the historical discipline as a discourse. Truly, he did not abandon the ideal that History as a discipline could accede to a kind of objectivity, which would be guaranteed by the joint action of the philological method, the interpretation and the empathy given by the process of understanding.